Approaches to Stylistics and the Literary Text - Elena-Maria Emandi (Association of Social and Educational Innovation, 2017)
The present study offers a theoretical overview of the approaches of style in a literary text. The main directions are presented in strict relation to their relevance to highlighting the specificity of a certain type of literary production. To well-known names of international stylisticians there have been added outstanding Romanian names whose contribution to the domain is considered undoubtedly valuable.